Prevalence and triage of first contact pelvic floor dysfunction complaints in male patients referred to a Pelvic Care Centre. Issue 4 (25th January 2015) - Berghmans, Bary; Nieman, Fred; Leue, C.; Weemhoff, M.; Breukink, S.; van Koeveringe, G.
Abstract : Aims: (i) To describe and analyse pelvic floor dysfunction symptoms in men referred to a Pelvic Care Centre (PCC). (ii) To describe the triage process of the same patients based on response to a first‐contact interview. Methods: Triage started with a telephone interview using previously constructed questions, asking for six types of PF complaints during the preceding 6 months. If present, complaint severity was registered on a 0–10 scale. Next, these first‐contact complaints were used to describe patient case mix profiles using cross‐tabular analysis. Later on, at first PCC visit, an intake questionnaire regarding specific PF health problem(s) was filled out. This procedure contributed to a firm baseline characterization of the individual patient profile and a clinically valid allocation to structured, predefined assessment and treatment. Results: From 2005 to 2013 985 first‐time patients (mean age 58.2 years (SD 15.3) have been referred to the PCC. Most frequently mentioned complaints: voiding dysfunctions (73.9%), urinary incontinence (29.5%), sexual problems (16.6%), faecal incontinence (13.9%), constipation (9.6%), and prolapse (0.3%). A first appointment to a single specialist was determined in 805 (81.7%) patients, in 137 (13.9%) consultation of >1 specialist. Data analysis revealed higher‐order interactions between PF complaints, suggesting patient profile complexity and patient population heterogeneity. Conclusions: One out of seven PCC patients showed multifactorial problems, needing >1 specialist. PF complaints either turned out to stand alone or cluster with others, or even to strengthen, weaken, nullify or inverse relationships. Neurourol. Urodynam. 35:487–491, 2016 . © 2015 Wiley Periodicals, Inc.